TWO NEW SPECIES OF DIPLOMMATINA BENSON, 1849 (GASTROPODA, CAENOGASTROPODA: DIPLOMMATINIDAE) FROM BORNEO - Vermeulen, Jaap J.; Mohd Zacaery, Khalik (The Association of Polish Malacologists, 2021)
Two new species of Diplommatina from limestone hills on Borneo are described: D. heteropleura sp. nov., from Sarawak (Malaysia) and D. stenoacron sp. nov., from East Kalimantan (Indonesia). The first is uniquely identified among the Bornean Diplommatina by the arrangement of radial ribs: widely spaced on all whorls except the last 1.5, where they are closely spaced; the second belongs to a small group of species without radial ribs but is larger than any of them.